HYPERTRIGLYCERIDAEMIA-INDUCED PANCREATITIS - Latt, Zin Myo; Aung, Moe Wint; Latt, Tint Swe (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE A 45-year-old male presented with a five-day duration of abdominal pain and yellow pustular skin eruptions on his eyebrow. His abdominal pain was worse after eating and was associated with nausea. The patient had diabetes mellitus since 37 years of age and receiving Gliclazide MR 60 mg twice daily and metformin 500 mg three times daily. He has a family history of diabetes, with his mother suffering from diabetes. He has a hepatitis B infection without current treatment. He was a previous smoker with a 10-pack-year history and stopped only 4 months prior. He has been an alcoholic beverage drinker (half a bottle of whisky) 3 days per week for the last 5 years. Physical examination revealed a fever of 102°F, tachycardia of 100, blood pressure of 130/70 mm Hg, respiratory rate of 16, and oxygen saturation of 96% on room air. He had abdominal tenderness in his right upper quadrant and epigastrium. His skin lesions were discovered to be eruptive xanthoma. Fundoscopy revealed a lipaemic retina. Blood tests revealed a triglyceride of 5460 mg/dl and cholesterol of 558 mg/dl, while liver function test was normal. Blood showed leukocytosis with neutrophil predominance and CRP was 229.04 mg/l. HbA1c was 8.9%. Amylase was initially 43 U/l, but when rechecked several hours later was 167 U/l. Blood glucose was 443 mg/dl. The abdominal x-ray and a chest x-ray revealed no abnormality. A USG of the abdomen showed an enlarged fatty liver and swollen pancreas. He was diagnosed with Hypertriglyceridemiainduced pancreatitis. The patient was kept nil by mouth and given aggressive fluid resuscitation alongside analgesia for pain review. His blood sugars were closely monitored as the VRII protocol had been started in the Emergency Department. An urgent CT scan was booked which confirmed pancreatitis. An insulin infusion FRII was started and an intravenous antibiotic was given. The patient made a good recovery and was followed up in the clinic for the management of his hyperlipoproteinemia.